Anto Tulim Pengaruh Promosi, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Alat Kesehatan Pada PT. Mitra bersama Sejahtera Abadi - Anto Tulim; Edy Firmansyah; Kelvin Meidi (Yayasan Literasi Sains Indonesia, 2022)
Purchasing decisions are influenced by promotion, price and quality of products. The company must ensure as many promotions as possible, prices that are able to compete with similar companies and maintain the quality of products so that they can still be used to improve purchasing decisions. Promotion is a form of marketing communication. Price is the amount of money needed in exchange for various combinations of goods and services. Product quality is a dynamic condition related to products, people and labor, processes or environments that comply with and exceed consumer expectations. Purchasing Decision is an integration process that combines knowledge to evaluate two or more alternative behaviors and choose one of them. Having a complete product, competitive prices and more promotions can improve purchasing decisions. The purpose of this research is to find out and analyze the influence of promotion, price and quality of products towards the decision to purchase medical devices at PT. Mitra Bersama Sejahtera Abadi. This research was conducted at PT. Mitra Bersama Sejahtera Abadi. The type of research used is descriptive quantitative. The results of this study showed that the promotion, price and quality of products simultaneously have a positive and significant effect towards purchasing decisions at PT. Mitra Bersama Sejahtera Abadi. In part, price has a positive and significant effect towards the decision to purchase medical devices at PT. Mitra Bersama Sejahtera Abadi while promotion and quality of products does not have a positive and significant effect towards medical devices purchasing decisions at PT. Mitra Bersama Sejahtera Abadi. In addition, testing of the adjusted determination coefficient was 0.764 meaning that promotion, price and quality of products had an effect of 76.4% towards purchasing decisions while the remaining 23.6% were influenced by other unexorded free variables such as service quality, location and brand image.